Band‐Like Charge Transport in Phytic Acid‐Doped Polyaniline Thin Films. (6th August 2021) - Ballabio, Marco; Zhang, Tao; Chen, Chen; Zhang, Peng; Liao, Zhongquan; Hambsch, Mike; Mannsfeld, Stefan C. B.; Zschech, Ehrenfried; Sirringhaus, Henning; Feng, Xinliang; Bonn, Mischa; Dong, Renhao; et al.
Abstract: We explore the charge transport properties of phytic acid (PA) doped polyaniline thin films prepared by the surfactant monolayer‐assisted interfacial synthesis (SMAIS). Structural and elemental analysis confirms the inclusion of PA in the thin films and reveals a progressive loss of crystallinity with the increase of PA doping content. Charge transport properties are interrogated by time‐resolved terahertz (THz) spectroscopy. Notably, independently of doping content and hence crystallinity, the frequency‐resolved complex conductivity spectra in the THz region can be properly described by the Drude model, demonstrating band‐like charge transport in the samples and state‐of‐the‐art charge carrier mobilities of ≈1 cm 2 V −1 s −1 . A temperature‐dependent analysis for the conductivity further supports band‐like charge transport and suggest that charge carrier mobility is primarily limited by impurity scattering. This work highlights the potential of PA doped polyaniline for organic electronics. Abstract : The interplay between conductivity and structure in polyaniline thin films doped by phytic acid is analyzed. While samples become less crystalline with doping content, even becoming amorphous, the conductivity for all samples is properly described using the Drude model. Temperature dependent analysis excludes the presence of thermally activated processes and suggest free charge carrier mobility being limited by impurity scattering.